IMPLEMENTASI CRM PADA SISTEM INFORMASI JUAL-BELI MOBIL DI SHOWROOM DEFFA JAYA MOTOR BERBASIS WEB - Erlan Darmawan; Rio Priantama; Koko Risnanto (Cloud Information, 2019)
The Deffa Jaya Showroom uses a conventional system in managing its products and customers. Conventional system causes inaccuracies in the management of goods, inventory and customer data. Increased loyalty is done by providing good service. This study aims to increase consumers’ loyalties through the application of CRM. This research uses the waterfall system development method. The stages of this waterfall are analyzing system requirements, making system designs, implementing systems, testing and operating and maintaining systems. Forms of CRM implementation that are applied to the Showroom are giving discounts on certain products and certain days, giving discounts on each cash purchase, a means of product discussion that is a means of communication between customers and the Deffa Jaya Motor Showroom in discussing about products that will be purchased by the customers, and a means of criticism provide criticism or suggestions for the Deffa Jaya Motor Showroom. The application of CRM in this system is expected to be able to improve services so that it impacts on increasing customer loyalty.